Policy effectiveness is limited by a flat Phillips curve, stabilization as practiced in Europe and the US - David M. Kiefer (The University of Utah, Department of Economics, 2016)
A standard model of activist macroeconomic policy derives a monetary reaction rule by assuming that governments have performance objectives, but are constrained by an augmented Phillips curve. In addition to monetary policy, governments apply a variety of instruments to influence inflation and output, including fiscal policy, bailouts and foreign exchange policy, but effectiveness is limited by Phillips curve flatness. Solving the Phillips curve and reaction rule for a reduced form, we study this theory with a panel of countries. A textbook version of the activist model leads to disappointing results; the activist model fits the data only slightly better than a flat-Phillipscurve benchmark. The econometric results are enhanced by accounting for autocorrelated shocks. Although results are mixed, our interpretation favors inertial inflation expectations over rational ones. An extension of this approach suggests that US policy is more effective than that of European governments, finding that the US Phillips curve is more than twice as steep.
Keywords: E61; E63; 330; stabilization policy; inflation targets; expectations